„Min hukommelse er som en tesi“: Om kvinder, kræft og kemoterapi - Hansen, Helle Ploug (Tidsskriftet Antropologi, 2005)
Helle Ploug Hansen: “My Memory is Like a Sieve”: On Women, Cancer and Chemo- therapy Empirical data from my research project about women, cancer and rehabilitation are used in this article to explore loss of memory in relation to a severe disease. First I describe how women experience loss of memory in the case of cancer, and how they interpret this as a side-effect of the chemotherapy treatment. Hereby they reproduce a part of the dominant health discourse, where loss of memory is understood as cognitive impairment. Second, I explore how the women through their stories of illness experiences show that they remember quite well and with a lot of details – they just remember something other than they thought they should remember. Third, I argue that people experiencing a severe disease concentrate a great deal of their attention on the body, forgetting acts and experiences outside their own living body. As Scarry has said: “What is remembered in the body is remembered well.”